Metataxonomic analysis of bacterial and fungal communities in colonial cheese - MYAZAKI, Natália Lima; CARDOSO, Mariana Freitas; VERRUCK, Silvani (Food Science and Technology, 2024)
Colonial cheese is one of the typical products of the southern region of Brazil, and it is known that this type of food is home to a complex microbial community. Therefore, this study aimed to evaluate the microbiota present in Colonial cheese, through the use of a high-performance system MiSeq Sequencing System, from the regions V3/V4 of the 16S rRNA using the 341F and 806R primers for bacteria and ITS1/ITS2 primers for the ITS1 region of molds and yeasts. Sequence analyses were performed using the Sentinel pipeline. The results for bacterial microbiome showed that there were 4 phyllo, 30 genera, and 57 species in the sample, among them Lactococcus lactis (30.63%), Corynebacterium variable (17.91%), Enterococcus sp. (17.4%), and Bifidobacterium psychraerophilum (7.24%), all naturally found in milk. In addition, 19 yeast species were identified, including Diutina catelunata, Clavispora lusitaniae, Kodamaea ohmeri, Kluyveromyces marxianus, and Candida ethanolica those that obtained the highest number of sequences reads. The results obtained on the microbiome are in line with other studies on cheeses across the globe, considering that the microorganisms are naturally found in both the raw material and the production environment.